2013
DOI: 10.1002/art.34646
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between pain and radiographic severity in knee osteoarthritis: Findings from quantitative sensory testing of central sensitization

Abstract: Objective Radiographic measures of the pathologic changes of knee osteoarthritis (OA) have shown modest associations with clinical pain. We sought to evaluate possible differences in quantitative sensory testing (QST) results and psychosocial distress profiles between knee OA patients with discordant versus congruent clinical pain reports relative to radiographic severity measures. Methods A total of 113 participants (66.7% women; mean ± SD age 61.05 ± 8.93 years) with knee OA participated in the study. Radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
335
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(374 citation statements)
references
References 48 publications
16
335
0
2
Order By: Relevance
“…There are many patients who have radiographic evidence of OA in the absence of pain and those who have little radiographic evidence of OA with moderate to severe pain. 31 Finan et al 32 suggested that central sensitization in knee OA is apparent among patients with high levels of pain in the absence of moderate-to-severe radiographic evidence of knee OA. In our study, there was significant correlation between painDETECT scores and the VAS score, but we found no correlation between painDETECT scores and the Kellgren-Lawrence grades.…”
Section: Discussionmentioning
confidence: 99%
“…There are many patients who have radiographic evidence of OA in the absence of pain and those who have little radiographic evidence of OA with moderate to severe pain. 31 Finan et al 32 suggested that central sensitization in knee OA is apparent among patients with high levels of pain in the absence of moderate-to-severe radiographic evidence of knee OA. In our study, there was significant correlation between painDETECT scores and the VAS score, but we found no correlation between painDETECT scores and the Kellgren-Lawrence grades.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is reported by 10% of subjects with normal radiographs, and 40-79% of patients with the significant radiographic joint abnormalities typical of OA (30). A number of studies indicate that only half of the patients with radiographic OA feel pain, and that there is a weak correlation between pain severity and radiographic changes (31)(32)(33)(34). Even studies showing significant associations between changes in joint structure and symptoms have found that 51% of the subjects with knee pain for >1 year do not show any typical radiographic joint changes, and that up to 50% of patients with the radiographic changes of OA have no symptoms (35).…”
mentioning
confidence: 99%
“…Of eleven studies [14][15][16][17][18][19][20][21][22][23][24], six at least showed a significant relationship between depression and pain, but these findings corresponded to evidence level IV because they were confirmed by cross-sectional studies; the results of the two cohort studies were not consistent. Pain catastrophizing had been measured by ten studies [14,15,19,20,23,[25][26][27][28][29] in our review and was shown to be related with pain worsening in six cross-sectional studies as evidence level IV and in one prospective cohort study as evidence level II. Self-efficacy was significantly related to pain worsening in four studies [16,25,27,30], and one study suggesting this finding …”
Section: Assessment Of the Risk Of Biasmentioning
confidence: 80%
“…RoBANS contains six domains: the selection of participants, confounding variables, the measurement of exposure, the blinding corresponded to evidence level II. Anxiety was investigated by five studies [14,18,19,28,31], one of these studies was of a prospective cohort design and showed no causal relationship with pain worsening. Three studies [19,26,28] examined the relationship with fear and pain worsening, but statistical significance was not confirmed.…”
Section: Assessment Of the Risk Of Biasmentioning
confidence: 99%